Overall Equipment Effectiveness (OEE) Analysis: A Case Study in the PVC Compound Industry - Bambang Setiawan; Fikri Al Latif; Erry Rimawan (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
PT. Riken Indonesia is a company engaged in PVC Compound that is specially designed to meet the needs of industrial markets such as automotive construction, household electronic toys, and high quality disposable medical devices. The sample chosen was line 5 The purpose of this study was to analyze the value of OEE including the Availability, Performance rate and quality rate. The method used is Overall Equipment Effectiveness with analysis of Six Big Losses. For the analysis of six big losses to the OEE value, namely the setup & adjustment value of 86.27%, the breakdown value of 9.06%, the idling & minor stop value of 2.67%, and the defect value of 2.01%. Set up & adjustment are the main thing from the problem of six big losses, the biggest setup and adjustment is influenced by cleaning time of 61.61%, startup/shutdown of 37.65%, and adjustment of 0.74%. Based on the analysis, the Availability rate of 76.72%, a performance rate of 84.66%, and a quality rate of 99.89%. The OEE is consists of availability rate, performance rate and quality rate, the OEE value was 64.88%, which means it was below the standard value that is 85%. So it can be said that the engine performance in line 5 PT. Riken Indonesia has not been effective and requires maintenance or continuous improvement.